2019
DOI: 10.1371/journal.pone.0218365
|View full text |Cite
|
Sign up to set email alerts
|

Honey bees (Apis mellifera spp.) respond to increased aluminum exposure in their foraging choice, motility, and circadian rhythmicity

Abstract: Aluminum is increasingly globally bioavailable with acidification from industrial emissions and poor mining practices. This bioavailability increases uptake by flora, contaminating products such as fruit, pollen, and nectar. Concentrations of aluminum in fruit and pollen have been reported between 0.05 and 670mg/L in North America. This is particularly concerning for pollinators that ingest pollen and nectar. Honey bees represent a globally present species experiencing decline in Europe and North America. Regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(50 citation statements)
references
References 68 publications
2
44
4
Order By: Relevance
“…The present study used a scaled‐down version from prior literature with larger flowers to control for MF gradient, and a reduction in the number of choices from 36 to 4 because of the number of observers required to conduct a full‐scale flower patch [Karahan et al, 2015]. Yellow and blue flower colors were chosen as bees typically have a strong strong preference for one or the other as opposed to a blue‐white comparison in which preferences can be manipulated [Chicas‐Mosier et al, 2017, 2019]. The white plastic board that supported the flowers was balanced on both MF generator disks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study used a scaled‐down version from prior literature with larger flowers to control for MF gradient, and a reduction in the number of choices from 36 to 4 because of the number of observers required to conduct a full‐scale flower patch [Karahan et al, 2015]. Yellow and blue flower colors were chosen as bees typically have a strong strong preference for one or the other as opposed to a blue‐white comparison in which preferences can be manipulated [Chicas‐Mosier et al, 2017, 2019]. The white plastic board that supported the flowers was balanced on both MF generator disks.…”
Section: Methodsmentioning
confidence: 99%
“…These insects are experiencing population decline, along with other pollinators as a result of pathogens, habitat destruction, and pesticide application [Goulson et al, 2015; Hallmann et al, 2017]. Honey bees have been used as a model organism to study responses to pesticide exposure, learning, neuroadaptation, and environmental impacts and have been shown to discriminate between MFs [Walker and Bitterman, 1989a,b; Abramson et al, 2012a; Williamson and Wright, 2013; Karahan et al, 2015; Chicas‐Mosier et al, 2019]. They also are easy to rear, manage, and allow for large sample sizes with similar environmental background conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of AChE can also result in physiological effects such as spasms, hyperactivity, and erratic movement [ 15 , 16 ]. Hyperactivity can disrupt the diurnal circadian rhythms of forager bees, which may cause them to miss key foraging times for specific plants [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ingestion of aqueous aluminum has been determined to affect floral foraging decisions made by honey bees [ 17 , 18 ]. Bees that were fed an aluminum solution exhibited reduced flexibility to changing floral environments [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Subspecies differences have been detected in the learning ability of Africanized and European subspecies (Abramson et al, 1997) and between Apis mellifera caucasica and Apis mellifera syriaca . In addition to subspecies differences in learning ability, it is also known that honey bee subspecies also differ in their antipredator behavior (Kandemir et al, 2012) and in behavior following exposure to other bioavailable substances (Chicas-Mosier et al, 2019). Further, evidence has shown that honey bees subject to passive avoidance paradigms can exhibit behavior altered by factors outside of the experimental session.…”
mentioning
confidence: 99%